Functional chromopeptide nanoarchitectonics: molecular design, self-assembly and biological applications - Chang, Rui; Zhao, Luyang; Xing, Ruirui; Li, Junbai; Yan, Xuehai (Chemical Society reviews, 2023)
Chromoproteins are a class of delicate natural compounds that elegantly complex photosensitive species with proteins and play a central role in important life processes, such as photosynthesis. Inspired by chromoproteins, researchers integrate simple peptides and photosensitive molecular motifs to generate chromopeptides. Compared with chromoproteins, chromopeptides exhibit a relatively simple molecular structure, flexible and adjustable photophysical properties, and a capability of programmable self-assembly. Chromopeptide self-assembly has attracted great attention as the resultant high-level architectures exhibit an ingenious combination of photofunctions and biofunctions. This review systematically summarizes recent advances in chromopeptide nanoarchitectonics with particular focus on the design strategy, assembly mechanism, and structure-function relationship. Among them, the effect of peptide sequences and the variation in photophysical performance are critically emphasized. On this basis, various applications, including biomedicine and artificial photosynthesis, are discussed together with the future prospects of chromopeptide nanoarchitectonics. This review will provide insights into chromopeptide nanoarchitectonics and corresponding materials with precise designs, flexible nanostructures and versatile functions. In addition, knowledge involving chromopeptide nanoarchitectonics may aid in the development of many other kinds of supramolecular biological materials and bioengineering techniques. An overview of chromopeptide self-assembly is presented to systematically understand this kind of newly emerging peptide building block.